Penipuan dan Restorative Justice dari Perspektif Kriminologi - Muh. Naim; Patahillah Asba; Bakhtiar Tijjang (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
This research was conducted to know the application of Restorative Justice in Fraud Cases at the Sidenreng Rappang Police and to find out the obstacles in the implementation of Restorative Justice at the Sidenreng Rappang Police. This research uses a normative-empirical type of research. The results of the study show that crime is seen as an act that harms others and damages social relationships. In contrast to criminal law which has withdrawn crime as a state problem and only the state has the right to punish, although indigenous communities can provide sanctions and the settlement of criminal cases of fraud through restorative justice at the Sidenreng Rappang Police does not abolish criminal acts because the case is only terminated by investigating reasons for not finding sufficient evidence. The termination of the investigation is stated in the Decision Letter on the Termination of Investigation which is followed up by the Order of Termination of Investigation (SP3). The SP3 can be reopened at any time if it is submitted for pre-trial by one of the parties so that with the order of a court decision, investigations of criminal acts of fraud whose investigations have been stopped can be reopened.